Anticoagulant effects of dabigatran in paediatric patients compared with adults: combined data from three paediatric clinical trials - Maas, Hugo; Brückmann, Martina (Thrombosis and haemostasis, 2018)
Background Physiological age-related changes in the haemostatic and coagulation systems result in differing anticoagulant assay responses to standard anticoagulants. Therefore, we investigated the response of anticoagulant assays to dabigatran etexilate (DE) in children compared with adults. Objective This article assesses the relationship between plasma dabigatran concentration and coagulation assay results across age groups in children and adults. Patients and Methods Data from three clinical trials in which children received DE following standard of care for venous thromboembolism were compared with data from adult clinical trials. The effects of dabigatran concentration on diluted thrombin time (dTT), ecarin clotting time (ECT) and activated partial thromboplastin time (aPTT) were analysed graphically and with modelling. Results The concentration-dTT relationships were consistent in children across all ages and adults in the graphical analysis. For ECT and aPTT, relationships based on ratios over baseline were similar across all ages; absolute clotting times showed that the same exposure resulted in longer clotting times in some of the children aged < 1 year versus adults. Modelling showed concentration-clotting time relationships for all three assays were largely comparable between adults and children, except in those aged < 2 months, in whom there was a slight upward shift in ECT and aPTT relative to adults. Conclusion Results suggest that developmental haemostatic changes will have little impact on response to DE. However, further paediatric clinical trials assessing the relationship between coagulation assay responses and clinical outcomes will be needed to confirm this finding.